2020
DOI: 10.14202/vetworld.2020.1988-1991
|View full text |Cite
|
Sign up to set email alerts
|

Contamination factors associated with surviving bacteria in Thai commercial raw pet foods

Abstract: Aim: This study aimed to identify the surviving bacteria in commercial raw pet food and to analyze the factors associated with their contamination. Materials and Methods: A total of 17 samples from 12 brands available in Thailand were randomly selected for analysis. Fifteen samples were frozen products and two were freeze-dried. The total bacterial counts (TBCs) of Clostridium perfringens, Campylobacter spp., Staphylococcus aureus, Escherichia coli, Salmonella spp., Listeria spp., and Listeria monocytogenes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…In recently published European studies, total ACC measured in RMBDs showed a wide range of bacterial contamination, from 7.9 × 10 2 to 7.4 × 10 8 CFU/g [ 11 , 13 , 15 ]. The high total ACC recorded in the present study is similar to the findings of a recent study from Thailand, where a median ACC score of 1.81 × 10 8 CFU/g was measured in 17 RMBDs [ 62 ]. High total ACC may cause rapid alteration of meat during cold storage due to microbial growth, protein degradation, and lipid oxidation.…”
Section: Discussionsupporting
confidence: 91%
“…In recently published European studies, total ACC measured in RMBDs showed a wide range of bacterial contamination, from 7.9 × 10 2 to 7.4 × 10 8 CFU/g [ 11 , 13 , 15 ]. The high total ACC recorded in the present study is similar to the findings of a recent study from Thailand, where a median ACC score of 1.81 × 10 8 CFU/g was measured in 17 RMBDs [ 62 ]. High total ACC may cause rapid alteration of meat during cold storage due to microbial growth, protein degradation, and lipid oxidation.…”
Section: Discussionsupporting
confidence: 91%
“…In one Swedish study, bacteria belonging to the family Enterobacteriaceae, including E. coli, was present at a level which exceeded EU regulations for raw meat intended for pet food production in 52% of RMD samples (Hellgren et al, 2019), and in a study from Switzerland, 73% of samples tested exceeded these limits (Nüesch-Inderbinen et al, 2019). This was also the case for frozen commercially available RMD in Thailand (Kananub et al, 2020) and in Italy, where samples were found to be contaminated with Salmonella spp., E. coli O157:H7, Listeria monocytogenes and Campylobacter spp., despite freezing (Bottari et al, 2020). In another study from Italy, RMD products purchased online and received frozen were found to be highly contaminated with E. coli immediately following defrosting, as well as having Listeria spp., Clostridia spp.…”
Section: Discussionmentioning
confidence: 96%
“…and Clostridium spp. ( Weese et al, 2005 ; Strohmeyer et al, 2006 ; Mehlenbacher et al, 2012 ; Nemser et al, 2014 ; Bojanić et al, 2017 ; Van Bree et al, 2018 ; Hellgren et al, 2019 ; Bottari et al, 2020 ; Kananub et al, 2020 ; Treier et al, 2021 ). In the United Kingdom there have been limited studies specifically investigating the presence of bacterial pathogens in RMD, however there have been a number of recalls involving RMD reported by the Food Standards Agency due to the presence of Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…A previous American study recovered ESBL-E from frozen but not from freeze-dried raw diets ( 11 ). This difference may exist because the reduced water content in freeze-dried foods creates suboptimal conditions for bacterial survival ( 11 , 23 ). It is also possible that different thawing methods may impact the quantity of bacteria recovered from frozen RMBDs.…”
Section: Discussionmentioning
confidence: 99%